A seguridade social na produção legislativa Brasileira do pós-1988 - Vieira, Fabiola Sulpino,Natalino, Marco Antonio Carvalho (Instituto de Pesquisa Econômica Aplicada, 2023)
The study aims to contribute to the debate on social welfare in Brazil through an analysis focused on the normative action of the State on the subject from October 1988 until September 2022. October 1988 marks the date when a new, democratic constitution was enacted, which defined social assistance, social security and health care as interconnected social rights of citizenship under the umbrella term social welfare. We carried out a content analysis of the legal production at the federal level, considering the general theme social welfare as the universe of analysis and each piece of federal legislation (constitutional amendments, laws, provisional laws, presidential decrees and legislative decrees) as units of analysis. The software Iramuteq was used to perform some of the content analysis, including descriptive statistics of frequent expressions, similitude analysis, correspondence factor analysis and descendant hierarchical classification (Reinert method). The most frequently addressed subject in this legislative production was the execution of the Social Welfare Budget (OSS), followed by its financing and/or taxation. We define this prominence of budgetary concerns as
10.38116/td2887-port
Keywords: Graue Literatur; social welfare; public policy; legislation; Federal Government; Brazil